Breakdown by disengagement: Tunisia’s transition from representative democracy - Kevin Koehler (Political Research Exchange, 2023)
ABSTRACTOn 25 July 2021, Tunisian president Kais Saied suspended parliament, lifted the immunity of its members, and dismissed the prime minister and the government. Tunisia’s post-revolutionary democracy had thus succumbed to a populist president within two years from his electoral victory in the context of widespread popular disillusionment with the entire political class. This article draws on the work of Peter Mair, in particular his analysis in Ruling the Void (2013), to understand democratic breakdown in Tunisia. I argue that political dynamics in Tunisia diverge significantly from the standard model of democratic backsliding. Instead, I conceptualize the Tunisian case as breakdown by disengagement. The relative success of Tunisian democratization after the 2014 elite compromise paradoxically fuelled a crisis of representation: The main political camps lost popular support, populist challengers were strengthened, and citizens disengaged from conventional politics in ever greater numbers. Popular disengagement and elite withdrawal into a sphere of competition protected by the elite pact gave rise to a void at the heart of Tunisian democracy. While Kais Saied’s anti-party project proposed to fill this void with an alternative political system built from the bottom up, there is growing evidence of authoritarian retrenchment instead of democratic renewal.